2020
DOI: 10.1097/aog.0000000000004010
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Maternal and Perinatal Mortality and Vertical Transmission in Pregnancies Complicated by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Co-V-2) Infection

Abstract: Chapter 1 Core principles and methods for conducting a systematic review of health interventions Chapter 2 Systematic reviews of clinical tests Chapter 3 Systematic reviews of public health interventions Chapter 4 Systematic reviews of adverse effects Chapter 5 Systematic reviews of economic evaluations Chapter 6 Incorporating qualitative evidence in or alongside effectiveness reviews APPENDICES: Appendix 1 Other review approaches Appendix 2 Example search strategy to identify studies from electronic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
222
0
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(289 citation statements)
references
References 120 publications
14
222
0
30
Order By: Relevance
“…Increased rates of preterm delivery, fetal compromise, and cesarean section have been reported in pregnancies complicated by COVID-19. 1,2,6,7 Complications in pregnancy were observed in approximately one-quarter of cases in the present study, consistent with the literature. 1,2,6,7 Some publications claimed that blood group A was associated with a higher risk of acquiring COVID-19 and blood group O was associated with a lower risk of infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased rates of preterm delivery, fetal compromise, and cesarean section have been reported in pregnancies complicated by COVID-19. 1,2,6,7 Complications in pregnancy were observed in approximately one-quarter of cases in the present study, consistent with the literature. 1,2,6,7 Some publications claimed that blood group A was associated with a higher risk of acquiring COVID-19 and blood group O was associated with a lower risk of infection.…”
Section: Discussionsupporting
confidence: 92%
“…1,2,6,7 Complications in pregnancy were observed in approximately one-quarter of cases in the present study, consistent with the literature. 1,2,6,7 Some publications claimed that blood group A was associated with a higher risk of acquiring COVID-19 and blood group O was associated with a lower risk of infection. 30,31 Although it was also found that blood group A was more common in positive cases, there was no case with an AB group unlike in the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been proposed that pregnant women should be considered a high-risk population, since gestation itself could be related with several pregnancy-related complications, higher susceptibility to respiratory pathogens and also can generate problems in terms of the spread of the infection due to the multiple interactions with the health-care system [2]. While initial evidence suggests that pregnant women were not at increased risk for COVID-19, neither developed a more severe disease compared to non-pregnant adults [3,4], recent reports suggest increased rates of preterm birth [5], pneumonia and intensive care unit admission [6], and maternal mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although direct evidence of viral positive reverse transcriptase-polymerase chain reaction (RT-PCR) were mostly negative in large majority of reported studies, the paucity of published data is limited with small cohort numbers , limited sensitivity and speci city of swab tests and rapid evolution of COVID-19 infection. [33][34][35][36]. Hence, more data is needed about the risk of vertical transmission before de nitive conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%